Balto-Slavic long vowels - Carrasquer Vidal, Miguel (Baltistica, 2013)
In Baltistica 46(1), Miguel Villanueva Svensson presents a defence of the so-called “traditional” view on the development of long vowels in Balto-Slavic, in opposition to the views of the “Leiden school” (see Frederik Kortlandt’s Long vowels in Balto-Slavic, Baltistica 21(2)). In Baltistica 47(2), Tijmen Pronk replies to Villanueva Svensson’s points. In this paper, the author would like to take some of the items discussed by Villanueva Svensson and Pronk and hold them against his own interpretation of the facts, which differs both from the Leiden and the “traditional” views. The following items are discussed: - Nom sg. of nouns ending in a resonant - Lithuanian -ė - Nouns with long root vowel: root nouns? - Nouns with long root vowel: vowel stems - Nouns with an acute diphthong - Pronominals - The Slavic (sigmatic) aorist - The Baltic ē-preterit - The Baltic future - Narten presents - ieškóti - Intensives /iteratives - je-presents